2 * sin (3 * x - п/4) = -√2;
sin (3 * x - п/4) = -√2/2;
3 * х - п/4 = (-1)^n * arcsin (-√2/2) + п * n, n ∈ Z;
3 * х - п/4 = (-1)^n * 3 * п/4 + п * n, n ∈ Z;
Найдем корни.
{ 3 * х - п/4 = 3 * п/4 + п * n, n ∈ Z;
3 * х - п/4 = п - 3 * п/4 + п * n, n ∈ Z;
{ 3 * х - п/4 = 3 * п/4 + п * n, n ∈ Z;
3 * х - п/4 = п/4 + п * n, n ∈ Z;
{ 3 * х = 3 * п/4 + п/4 + п * n, n ∈ Z;
3 * х = п/4 + п/4 + п * n, n ∈ Z;
{ 3 * х = п + п * n, n ∈ Z;
3 * х = п/2 + п * n, n ∈ Z;
{ х = п/3 + п/3 * n, n ∈ Z;
х = п/6 + п/3 * n, n ∈ Z.
Пошаговое объяснение:
долго я печатала.
А=3б
3б+5б+22/3б+б+11=9б+11+22/3б
А вообще такое ощущение что перед 11 должно быть оавно